1995
DOI: 10.1108/eb028835
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning: Dimensions for a Theory

Abstract: Organizational learning (OL) is receiving increasing attention from researchers and practitioners alike. In fact, some have suggested that the only sustainable competitive advantage is a firm's ability to learn faster than its competitors. In spite of OL's promise, the field has been slow to evolve. The primary impediments to the development of OL theory are that inconsistent terminology is used for comparable concepts and that different definitions are used to describe the phenomenon. Furthermore, many theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
238
2
34

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(277 citation statements)
references
References 20 publications
3
238
2
34
Order By: Relevance
“…Organizational learning is a process of absorbing new knowledge and information to improve enterprises' behavior (Crossan, Lane, White & Djurfeldt, 1995). Senge (1990) held that members' learning was an effective method to unite and create knowledge.…”
Section: The Intermediary Role Of Organizational Learningmentioning
confidence: 99%
“…Organizational learning is a process of absorbing new knowledge and information to improve enterprises' behavior (Crossan, Lane, White & Djurfeldt, 1995). Senge (1990) held that members' learning was an effective method to unite and create knowledge.…”
Section: The Intermediary Role Of Organizational Learningmentioning
confidence: 99%
“…It is unclear whether these differences highlight the specific aspects of organizational learning that are important for different groups of stakeholders, or whether they merely indicate actual exposure levels to the intervention and its consequences. Indeed, at the core of organizational learning theory is the idea that learning occurs at all levels, from the individual to the group and the organization (Crossan et al, 1995, Crossan et al, 1999, Marsick and Watkins, 2003. Developing organizational learning requires strength at all these levels (Marsick and Watkins, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have suggested that organizational learning occurs at three levels: the individual, the group, and the organization (Crossan et al, 1995, Crossan et al, 1999, Marsick and Watkins, 2003. Correspondingly, seven distinct but interrelated dimensions of a learning organization have been proposed (Marsick and Watkins, 2003, Yang, 2003, Yang et al, 2004.…”
Section: Organizational Learningmentioning
confidence: 99%
“…Zatímco na prahu devadesátých let byly výzkumné texty zaměřené na organizační učení spíše ojedinělé, dnes je nabídka takto založených publikací velmi široká (srov. Argyris, 1992;Crossan et al, 1995Crossan et al, , 1999Dodgson, 1993;Easterby-Smith, 1997;Fiol & Lyles, 1985;Huber, 1991;Levitt & March, 1988;Miller, 1996;Sun & Scott, 2003 aj. ).…”
Section: úVodunclassified
“…Crossan et al, 1995) a otevírají tím otázku, k čemu má organizační učení vést. V užších vymezeních vede organizační učení k odhalování a korekci chyb, zvládání problémů v činnosti či rozhodování (např.…”
Section: úVodunclassified